Transport and Barrier Functions in Rainbow Trout Trunk Skin Are Regulated by Environmental Salinity - Doyle, D.; Carney Almroth, B.; Sundell, K.; Simopoulou, N.; Sundh, H. (Frontiers in Physiology, 2022)
The mechanisms underpinning ionic transport and barrier function have been relatively well-characterised in the gills of teleost fish. In contrast, these processes remain much less clear for the trunk skin. In this study, we measured barrier function and active transport in the trunk skin of the rainbow trout, using the Ussing chamber technique. The effects of epithelial damage, skin region, salinity, and pharmacological inhibition were tested. Skin barrier function decreased significantly after the infliction of a superficial wound through the removal of scales. Wound healing was already underway after three hours and, after 24 hours, there was no significant difference in barrier function towards ions between the wounded and control skin. In relation to salinity, skin permeability decreased drastically following exposure to freshwater, and increased following exposure to seawater. Changes in epithelial permeability were accompanied by salinity-dependent changes in TEP and SCC. We propose that barrier function in rainbow trout trunk skin is regulated by tight junctions that rapidly respond to changes in salinity. The changes in TEP and SCC also suggest the presence of an active transport component. Immunostaining and selective inhibition suggest that one active transport component is an apical V-ATPase. However, further research is required to determine the exact role of this transporter in the context of the trunk skin.